Emergency department visits among people with cancer: Frequency, symptoms, and characteristics. Issue 3 (1st May 2021) - Gallaway, Michael Shayne; Idaikkadar, Nimi; Tai, Eric; Momin, Behnoosh; Rohan, Elizabeth A.; Townsend, Julie; Puckett, Mary; Stewart, Sherri L.
Abstract: Objective: People with cancer are increasingly more likely to visit an emergency department for acute care than the general population. They often have long wait times and more exposure to infection and receive treatment from staff less experienced with cancer‐related problems. Our objective was to examine emergency department (ED) visits among people with cancer to understand how often and why they seek care. Methods: We conducted a retrospective study of ED visits using the National Syndromic Surveillance Program BioSense Platform. Cancer reported during an ED visit was identified using International Classification of Diseases, Tenth Revision codes for any cancer type, including bladder, breast, cervical, colorectal, kidney, liver, lung, ovary, pancreas, prostate, or uterine cancers. Symptoms prompting the visit were identified for people with cancer who visited EDs in the United States from June 2017 to May 2018 in ≈4500 facilities, including 3000 EDs in 46 states and the District of Columbia (66% of all ED visits during a 1‐year period). Results: Of 97 million ED visits examined, 710, 297 (0.8%) were among people with cancer. Percentages were higher among women (50.1%) than men (49.5%) and among adults aged ≥65 years (53.6%) than among those ≤64 years (45.7%). The most common presenting symptoms were pain (19.1%); gastrointestinal (13.8%), respiratory (11.5%), and neurologic (5.3%) complaints; fever (4.9%); injury (4.1%); and bleeding (2.4%). Symptom prevalence differed significantly by cancer type. Conclusions: The Centers for Medicare & Medicaid Services encourages efforts to reduce acute care visits among people with cancer. We characterized almost 70% of ED visits among this population.